Pentingnya Memisahkan Pos Keuangan untuk IP dan MU (Investasi Pribadi dan Modal Usaha) - Kusumastuti, Anggit Dyah; Kartinawati, Erwin; Nolani, Viona Sebastian (Universitas Pahlawan Tuanku Tambusai, 2026)
The Traditional Herbal Medicine Craftsman UKM (UKM) in Kismoyoso Village, Boyolali, is a traditional herbal medicine business that has been passed down from previous generations and has been able to survive the onslaught of a wider variety of modern beverages. The problem faced by partners is that many entrepreneurs who started their businesses from scratch still have difficulty separating personal funds from business matters. The purpose of this PKM is to provide education on the importance of financial literacy, particularly in the aspect of separating personal finances from business capital. The methods used include preparation, implementation, and evaluation stages related to measuring the extent of participants' understanding and ability to manage their business finances. This approach is carried out as an effort to explain several simple strategies in separating IP and MU (personal investment and business capital) financial posts. The result of this community service activity is the ability of partners to manage finances by separating personal investments (IP) and business capital (MU). The separation is carried out through bookkeeping by recording business income and expenses so that it looks structured and neat.